Using satellite imagery to assess the glacier retreat in King George Island, Antarctica - Ibeth Rojas-Macedo; Cinthya Bello; Wilson Suarez; Edwin Loarte; Fiorella Vega-Jacome; Maria G. Bustamante Rosell; Pedro M. Tapia (Revista de Teledetección)
In recent decades, remote sensing has become a powerful tool for continuously monitoring glacier dynamics in remote areas, enabling the identification of significant spatiotemporal changes due to its capacity to provide multitemporal information at regional and global scales. In this study, Landsat satellite images (1989–2020) were used to quantify glacier retreat in the ice cap of King George Island (KGI), located in the Antarctic Peninsula, and to evaluate the teleconnections of El Niño – Southern Oscillation - ENSO (ONI and SOI indices) with climatic variables (temperature and precipitation) in this region. Our findings reveal a 10% loss in glacier coverage over the last 31 years, with a slower glacier retreat observed since 2008. Glaciers with smaller areas and marine terminating were the most affected. Of the 73 glaciers on KGI, 42% had continental terminating, 21% had marine terminating, and 37% had mixed terminating (continental and marine). Of the total glacier area lost, 35% corresponds to glaciers with marine terminating, while 16% corresponds to glaciers with continental terminating. Furthermore, climatic variables exhibited heterogeneous responses during ENSO events, with a significant correlation between mean temperature and ONI at the annual level and during the austral spring, which may be influencing glacier retreat in the study area to some extent.